TERRA transcription destabilizes telomere integrity to initiate break-induced replication in human ALT cells - Bruno Silva; Rajika Arora; Silvia Bione; Claus M. Azzalin (Nature Communications, 2021)
Abstract Alternative Lengthening of Telomeres (ALT) is a Break-Induced Replication (BIR)-based mechanism elongating telomeres in a subset of human cancer cells. While the notion that spontaneous DNA damage at telomeres is required to initiate ALT, the molecular triggers of this physiological telomere instability are largely unknown. We previously proposed that the telomeric long noncoding RNA TERRA may represent one such trigger; however, given the lack of tools to suppress TERRA transcription in cells, our hypothesis remained speculative. We have developed Transcription Activator-Like Effectors able to rapidly inhibit TERRA transcription from multiple chromosome ends in an ALT cell line. TERRA transcription inhibition decreases marks of DNA replication stress and DNA damage at telomeres and impairs ALT activity and telomere length maintenance. We conclude that TERRA transcription actively destabilizes telomere integrity in ALT cells, thereby triggering BIR and promoting telomere elongation. Our data point to TERRA transcription manipulation as a potentially useful target for therapy.